Considerations for implementing oral preexposure prophylaxis: a literature review. - Sowicz, Timothy Joseph; Teitelman, Anne M; Coleman, Christopher Lance; Brawner, Bridgette M (The Journal of the Association of Nurses in AIDS Care : JANAC, 2014)
Oral preexposure prophylaxis (PrEP) is in its infancy as an approved biomedical intervention; therefore, research is needed to understand the issues surrounding its implementation. The purpose of this literature review is to report the empirical research about PrEP to identify the salient issues surrounding its implementation. PubMed, Medline, and CINAHL databases were searched, yielding 45 articles meeting inclusion criteria for the review. Overall, we found patient awareness of PrEP varied and its use was low. Awareness was higher among providers. Patients were willing to use PrEP, but both patients' and providers' concerns may have impacted implementation of this intervention. PrEP requires a prescription, yet only five of the 45 articles addressed provider-level factors. Research involving providers is needed to ensure that patient risk of becoming infected with HIV is accurately assessed, that PrEP is provided to those at high risk for HIV infection, and that frequent follow-up is conducted.
Keywords: Anti-Retroviral Agents; Antibiotic Prophylaxis; Female; Health Knowledge, Attitudes, Practice; Health Personnel; Health Services Needs and Demand; HIV Infections; Humans; Patient Acceptance of Health Care; Pre-Exposure Prophylaxis